Recanalization with Stent-Retriever Devices in Patients with Wake-Up Stroke - Stampfl, S. (AJNR Am J Neuroradiol, 2013)
BACKGROUND AND PURPOSE: Stent-retriever devices play an increasing role in the interventional treatment of acute stroke patients, because fast recanalization can be achieved. The purpose of this study was to evaluate the feasibility of stent-retriever recanalization in patients with wake-up stroke in the anterior circulation. MATERIALS AND METHODS: We retrospectively analyzed clinical and angiographic data of 19 consecutive patients with wake-up stroke who were treated with stent-retriever devices between 2009 and October 2011. Recanalization was assessed by using the Thrombolysis in Cerebral Infarction score. Clinical outcome was evaluated at discharge and after 90 days by using the modified Rankin Scale. RESULTS: Median NIHSS score at admission was 17 (IQR, 15–20). Before the procedure, the TICI score was 0 in 18 patients and 1 in 1 patient. Recanalization with stent-retriever devices was successful (TICI ≥ 2) in 94.7%. Mean time to flow restoration was 36.7 minutes and to complete recanalization 83.7 minutes. Symptomatic intracranial hemorrhage occurred in 4 patients (21.1%). Eight patients had an NIHSS improvement of ≥4 points between admission and discharge. After 90 days, 2 (10.5%) of our patients presented with mRS 0–2; seven (36.8%) died. CONCLUSIONS: Despite successful and rapid recanalization with stent-retriever devices, good clinical outcome in patients with wake-up stroke is achieved in a minority of patients. Clinical outcome remains poor. Bleeding rates were higher compared with recanalization procedures within 6 hours after stroke onset.